The Attitude of the University of Baghdad Students towards the Mixed and Single-Sex Learning (Journal of the College of Education for Women, 2019)
The study aims at finding out:1. The students' attitude towards the mixed learning at the university.2. The statistically significant differences in attitude towards the mixed learning at the university according to the specialization variable.3. The statistically significant differences in attitude towards the mixed learning at the university according to the gender variable.The researcher has constructed a scale for measuring the students' attitude towards the mixed learning at the university.After assuring its validity and reliability, the scale has been given to a sample of (100) students. The sample is selected randomly from (4) colleges of the university of Baghdad, (2) for scientific specialization and (2)for humanities.The two independent samples T-test, person correlation coefficient and Alpha- Crombach are used to find out the results.The results show that:1. The students have mid-level attitude towards mixed learning at the university.2. There are statistically significant differences in the attitude towards the mixed learning according to the variable of specialization (scientific-humanities) in favor to humanities.3. There are statistically significant differences in the attitude towards the mixed learning according to the variable of gender in favor to female.Accordingly, several recommendations and suggestions have been set forward.